Impact of agricultural and oil activities on the natural covers of the Samaria oil field, Tabasco - Ramos Reyes, Rodimiro; Palomeque de la Cruz, Miguel Ángel; Zavala Cruz, Joel (Revista Mexicana de Ciencias Agrícolas, 2021)
In the tropical regions of southeast Mexico, subsistence productive activities, the growth of cities and the oil industry are occupying original covers of jungle vegetation, hydrophytic vegetation and bodies of water. The objective of the study was to assess the effect caused by the growth of primary and oil extraction activities on natural covers by modeling the change of land use in the Samaria oil field in the municipalities of Cunduacán and Centro, Tabasco, Mexico. A spatial analysis was performed with land occupation maps by means of Land Change Modeler and gains, losses, contributions, net change and transitions of each category were determined. From the beginning of oil extraction in 1965 until 2019, in the SOF, with an area of 8 052 ha, 647 ha of wetlands and 436 ha of arboreal vegetation disappeared, as a result of the expansion of primary activities and the oil industry, which occupied 1 287 ha of agricultural use, 1 598 ha of livestock use, 269 ha of oil infrastructure and 775 ha of urban area. It is concluded that the application of Land Change Modeler was novel for the evaluation of the degradation of ecosystems and the estimation of the distribution of the change of natural covers and artificial uses in the Santamaria oil field, state of Tabasco.